THE IMPLEMENTATION OF HERRINGBONE TECHNIQUE TO IMPROVE STUDENTS READING COMPREHENSION - Nurhasina Nurhasina; Sultan Baa; Maemuna Muhayyang (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The objective of the study was to determine whether or not using herringbone technique increased students' reading comprehension. The pre-experimental design technique was employed in this study. The population in this study was Grade 9 students of SMP Telkom Makassar 2022/2023 academic year. Twenty nine (29) students were selected as samples of the study using cluster random sampling technique.  The results of statistical analysis at the level of significant (a) 0.05 with a degree of freedom (df) = 28 and a p value (sig.2- tailed ) of 0.000 showed a significant difference between the pre-test and post-test results of the students exams. In other words, the results of the sig.2 tailed of the students post test were greater than the level of significance (0.000<0.05. It can be concluded that the use of Herringbone techniques could improve the EFL students’ reading comprehension. Keywords— implementation, herringbone techniques, improving, reading comprehension